A complete sequence of mitochondrial genome of Neolamarckia cadamba and its use for systematic analysis - Xi Wang (Nature Portfolio, 2021)
Abstract Neolamarckia cadamba is an important tropical and subtropical tree for timber industry in southern China and is also a medicinal plant because of the secondary product cadambine. N. cadamba belongs to Rubiaceae family and its taxonomic relationships with other species are not fully evaluated based on genome sequences. Here, we report the complete sequences of mitochondrial genome of N. cadamba, which is 414,980 bp in length and successfully assembled in two genome circles (109,836 bp and 305,144 bp). The mtDNA harbors 83 genes in total, including 40 protein-coding genes (PCGs), 31 transfer RNA genes, 6 ribosomal RNA genes, and 6 other genes. The base composition of the whole genome is estimated as 27.26% for base A, 22.63% for C, 22.53% for G, and 27.56% for T, with the A + T content of 54.82% (54.45% in the small circle and 54.79% in the large circle). Repetitive sequences account for ~ 0.14% of the whole genome. A maximum likelihood (ML) tree based on DNA sequences of 24 PCGs supports that N. cadamba belongs to order Gentianales. A ML tree based on rps3 gene of 60 species in family Rubiaceae shows that N. cadamba is more related to Cephalanthus accidentalis and Hymenodictyon parvifolium and belongs to the Cinchonoideae subfamily. The result indicates that N. cadamba is genetically distant from the species and genera of Rubiaceae in systematic position. As the first sequence of mitochondrial genome of N. cadamba, it will provide a useful resource to investigate genetic variation and develop molecular markers for genetic breeding in the future.